KONSENTRASI HAMBAT MINIMUM (KHM) KADAR SAMPEL ALANG-ALANG (Imperata cylindrica) DALAM ETANOL MELALUI METODE DIFUSI CAKRAM - Mulyadi, Moh (Chem Info Journal, 2013)
Bacteria are microorganisms arround us. Recent study was sought an alternative source that serves as an antibacterial because some pathogenic bacteria to be resintant with antibacterial. Materials are reported to have antibacterial activity among the reeds. Reed efficacious drug for acute kidney inflammation, antibacterial, vomiting blood, gonorrhea, and nosebleeds. This study aimed to obtain the Minimum Inhibitory Concentration (MIC) of the sample degree as an antibacterial reeds and obtain the data most potent antibacterial activity of the sample degree against the reeds to Escherechia coli, Pseudomonas aeroginosa, Staphylococcus aureus and Bacillus subtilis. One of the methods method used is the preformance test antibacterial paper disk diffusion method. This method is done by placing a paper disc that had been soaked in the test solution on solid media has been inoculated with the bacteria test. Once inoculated, the bacterial growth was observed to see the clear zone around the disc. Zone inhibitation that is formed around the discs at the lowest concentration of antibacterial is the MIC. MIC from the sample degree of the reeds against Escherechia coli bacteria, Pseudomonas aeroginosa, Staphylococcus aureus and Bacillus subtilis in a row of leaf sample degree in ethanol by 7%, 7%, 8% and 9%, for the sample degree flowers in ethanol of interest at 7%, 7%, 9% and 7%, and for the sample degree roots in ethanol of 7%, 8%, 10% and 8%. The third sample degree of reeds showed a good potential to inhibite bacteria Escherichia coli. The sample degree of leaves and flowers are more potential than roots of reeds to inhibite Pseudomonas aeroginosa. On the other hand, the most potential for